BURN PATIENTS IN REGIONAL PUBLIC HOSPITAL : PROFILE AND TREATMENTS OPTIONS IN REGIONAL PUBLIC HOSPITAL DR. DJASAMEN SARAGIH, PEMATANG SIANTAR FROM PERIOD 2017 - 2019 - Anggriant, Vincent; Saragih, Rajin; Pinem, Sersanta (E-Jurnal Medika Udayana; Vol 11 No 6 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i06.P15, 2022)
ABSTRACT Background : Burns are one of the types of trauma which high morbidity and mortality. Burns make skin tissue damaged by various causes such as flame, scald or hot water, electricity, chemicals, and radiation, which still often occur today. Burns are a common health problem in developing and poor countries. The epidemiology of burns that occurs in Indonesia is still quite rarely reported. Purpose and Objectives :   This study is to report burns at dr. Djasamen Saragih Regional Public Hospital, is a type B regional hospital in North Sumatra, Indonesia. Methods : This is descriptive analysis with cross-sectional by using medical records of burn patients treated from January 2017 to December 2019. The data are presented in tabular and graphic form. Results : There were 68 samples in this study. The highest incidence of burns was found in the adult age group as many as 46 cases (67,6%) and dominated by men of 45 persons (66,2%), with the most cases being caused by burns due to scalding injury 39 cases (57,4%). The majority of incidents in this study suffered from second-degree burns, recorded 61 cases (89,7%). Excisional debridement is the most common surgery performed therapy in as many as 42 cases (62%) in this study. Conclusions : From this study, it was shown that the high-risk groups in cases of burns were adults and men. The number of events that cause high morbidity and mortality can be prevented by increasing knowledge of burns, and implementing preventive measures, especially in low socio-economic communities.    Keywords : Burns, age, sex, etiology, degree, treatments